Planificación, Gestión Y Control Del Proyecto – Ampliación Open Plaza Piura III - Irigoin Cobeñas, Franz Segundo (2018)
The present experience was carried out in the work Open Plaza Piura III expand, developed by the company Steelwork Ingenieros S.A.C. and it's about project management. This work was carried out between June and August 2015 and was won in a private tender that was developed by the client G.P.I. Falabella Peru, whose purpose was to find a company that makes metal structures in this work. This paper shows the coordination, work and contributions made as a project manager, since an industrial engineer has the necessary skills to develop in an efficient and professional manner, thanks to the fact that the industrial engineer studies operations research, and the projects are a branch of that field of study The professional work function was developed where the professional reality of the industrial engineer was discussed, the theoretical and conceptual framework that is necessary to develop this report on project management and the objectives that are to be achieved. The experience report in the professional field was developed as project manager of the Expansion Open Plaza Piura III project. The events were described from when the invitation to the private tender was achieved until the work was won. After that, the key aspects to achieve an adequate management as described by the PMI are described, which are the aspects of scope, cost and time. Each one of them is mentioned and described from his concept in general until he understands each one in the work analyzed. The S Curve and the Ms Project are described as tools for project management. We talk about them from their concept, how they were used and what were used in this work. The usefulness of the PMBOK Guide and how it was used in this work is described, the formats that were developed and which each of them contains. Everything used and developed for the work Expansion Open Plaza Piura III can be seen in the annexes of this report. Finally, conclusions were drawn from this report, recommendations based on the description of this report to take into account in project management and recommendations for future industrial engineers, all based on project management.